The Importance of Formulating Objectives and Mastery of Learning Materials to Improve Students' Literacy Skills - Mahardika, I Ketut; Yusmar, Firdha; Firdausi, Soraya; Astuti, Sri Rejeki Dwi; Maghfiroh, Vella Amelia; Salsabila, Wilda Robiah; Sandria, Nazua Imel (Peneliti.net, 2024)
Literacy ability is a fundamental skill that is very important in modern education. Literacy not only includes the ability to read and write, but also critical thinking skills, analysis and evaluation of information. This research aims to highlight the importance of formulating specific learning objectives and mastery of material in improving students' literacy skills. By using a qualitative approach based on literature studies, this research found that clear learning objectives and mastery of the material contributed to increased motivation, student engagement and critical thinking abilities. It is hoped that the results of this research can become a reference for developing learning strategies in Indonesia